IMPLEMENTATION OF MULTI-AKAD STRUCTURES IN SHARIA PEER-TO-PEER LENDING PLATFORMS: A STUDY ON LEGAL COMPLIANCE AND INNOVATION IN INDONESIA’S FINTECH ECOSYSTEM - Zustika, Anisa Fadilah; Widiastuti, Tika; Bonang, Dahlia (Universitas Islam Negeri Mataram, 2025)
In the era of Society 5.0, the development of digital technology has increasingly influenced Indonesia’s financial sector, particularly through financial technology (fintech). This study explores the implementation of multi-akad (multiple contract structures) in Sharia Peer-to-Peer (P2P) Lending platforms in Indonesia. Using a qualitative case study method supported by in-depth interviews and documentation, the study identifies and analyzes contract types such as Qardh, Wakalah bil Ujrah, and Mudharabah Mutlaqah as applied within P2P lending schemes. Findings show that multi-akad practices, specifically categorized under al-‘Uqud al-Mujtami’ah, not only support Sharia compliance but also demonstrate innovation in adapting Islamic jurisprudence to contemporary digital finance. The study contributes to regulatory strengthening, offering insights to policymakers, platforms, and stakeholders in developing inclusive and ethical Sharia-compliant fintech ecosystems.